"It's in Your Heart": How the California Mini-Corps Program and Hispanic Serving Institutions are Transforming Migrant Student Education. Issue 3 (3rd July 2018) - Ginsberg, Alice; Gasman, Marybeth; Samayoa, Andrés Castro
ABSTRACT: This paper provides a deep dive case study of the California Mini-Corps Program within the context of an Hispanic Serving Institution.